2016
DOI: 10.1055/s-0036-1582446
|View full text |Cite
|
Sign up to set email alerts
|

Epidermoid Cyst Located in the Fourth Ventricle: Case Report and Review

Abstract: Epidermoid cyst is a congenital benign lesion, rarely seen in the topography of the fourth ventricle. The authors report a case of a 48-year-old patient with headache and cerebellar ataxia due to an epidermoid cyst in the fourth ventricle. We performed a surgical resection with histopathological confirmation of the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
(27 reference statements)
0
5
0
3
Order By: Relevance
“…The treatment of this condition includes repeated lumbar punctures and corticoids. 15 This situation was not observed in the case of the patient in question.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The treatment of this condition includes repeated lumbar punctures and corticoids. 15 This situation was not observed in the case of the patient in question.…”
Section: Discussionmentioning
confidence: 84%
“…In the case of incomplete removal of the lesion, the growth of the remnant tumor is as slow as that of the primitive tumor, requiring annual follow-up through magnetic resonance imaging to evaluate its development potential. 15 Some studies have indicated radiotherapy as an alternative to the failure in surgical treatment or recurrence, and tumor control can be achieved through this method. 16…”
Section: Discussionmentioning
confidence: 99%
“…O tratamento ideal é a exérese completa da lesão 3,4,9,25,29 . Em nosso caso, este procedimento foi realizado através de uma craniectomia suboccipital mediana, com remoção total da lesão, procedimento também realizado por outros autores 4,15,20,30 . Quando da realização da sua exérese total, apresenta bom prognóstico 2 .…”
Section: Discussionunclassified
“…Os sintomas de CE são geralmente aqueles de efeito de massa lento 3,5,19 . O quadro clínico quando localizado na fossa posterior é cefaleia e distúrbio da marcha 4,8 , como nosso paciente. Conforme o tamanho e evolução podem apresentar disfagia e diplopia por envolvimento de nervos cranianos 17 .…”
Section: Relato De Casounclassified
See 1 more Smart Citation